Characterization of some aflatoxin-deficient mutants of Aspergillus parasiticus - M. A. Moreno; M. C. Ramos; G. Suarez (Fungal Genetics Reports, 1993)
Aflatoxins are polyketide secondary metabolites produced by isolates of Aspergillus flavus and A. parasiticus. Since 1960, when a wide toxic outbreak was associated with moldy feed contaminated with aflatoxins, many efforts have been concentrated on this topic because of both the carcinogenic properties of these mycotoxins, and the worldwide occurrence of aflatoxin-producing fungi in cereal, cereal products and other agricultural commodities.